2022
DOI: 10.1002/adfm.202209354
|View full text |Cite
|
Sign up to set email alerts
|

High Performing Solid‐State Organic Electrochemical Transistors Enabled by Glycolated Polythiophene and Ion‐Gel Electrolyte with a Wide Operation Temperature Range from −50 to 110 °C

Abstract: The development of organic electrochemical transistors (OECTs) capable of maintaining their high amplification, fast transient speed, and operational stability in harsh environments will advance the growth of next-generation wearable and biological electronics. In this study, a high-performance solidstate OECT (SSOECT) is successfully demonstrated, showing a recorded high transconductance of 220 ± 59 S cm −1 , ultrafast device speed of ≈10 kHz with excellent operational stability over 10 000 switching cycles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…With their noninvasive nature, real‐time monitoring capability, and portability, solid‐state wearable OECT sensors could play a vital role in personal health monitoring, clinical diagnosis, and treatment. [ 24,25 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With their noninvasive nature, real‐time monitoring capability, and portability, solid‐state wearable OECT sensors could play a vital role in personal health monitoring, clinical diagnosis, and treatment. [ 24,25 ]…”
Section: Introductionmentioning
confidence: 99%
“…With their noninvasive nature, real-time monitoring capability, and portability, solid-state wearable OECT sensors could play a vital role in personal health monitoring, clinical diagnosis, and treatment. [24,25] It is also well known that the high transconductance of OECT translates to increased sensitivity; one strategy to improve the ion sensitivity is to tune the ionic-electronic conduction properties of channel material PEDOT:PSS. [14,26] A common method is to incorporate non-ionic surfactants, ionic liquids, high polar organic solvents, or acids into PEDOT:PSS, resulting in a highly conducting OECT channel.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SEOECT showed a slower transient speed with τ ON /τ OFF of 748±79/89±11 ms, which should be ascribed to the increased ionic resistance in the gel electrolyte relative to 0.1 m NaCl electrolyte. [ 28 ] Importantly, the d‐gdiPDI‐based SEOECT exhibited high operational stability with no degradation in its initial channel current after 1 h of pulse measurement (Figure 5d). These data indicated that d‐gdiPDI‐based OECTs in combination with solid electrolytes might hold promise in the field of flexible electronics for real‐time biosensor applications such as monitoring of low electrophysiological signals.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] In addition, the OECT based on solid or gel electrolytes is also highly sought after as it broadens its application scope and shows promise as flexible and wearable electronics. [24][25][26][27][28] In order to realize a high-transconductance OECT, the organic semiconductor channel layer is supposed to have a combination of high charge carrier mobility, preferably with a densely packed crystalline film morphology, and high charge storage capacity that largely depends on facile ion diffusion into the channel. Impressively, the past few years have witnessed a rapid expansion of the library of new materials and significant advances in the pursuit of these two properties, thanks to the synthetic strategy of grafting oligo ethylene glycol (OEG) sidechains onto traditional excellent electron-and hole-transporting backbones to facilitate ionic intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reports of IL-based gels with either organic or inorganic host networks in 2005, 8,9 much effort has been dedicated to the research on IL-based gels, which have been applied in many fields, such as energy storage, bioelectronics, sensors, and actuators. [10][11][12][13][14] Among these reported works, several naming systems have been found, such as ionic liquid gels, 15 ionogels, 16 ion gels, 17,18 ion-gels 19 and iongels, 20 which make it difficult to reference. In this review, we will adapt ionogels as the name.…”
Section: Introductionmentioning
confidence: 99%